2011
DOI: 10.3928/01484834-20110415-06
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Concept Map Teaching on Students’ Critical Thinking and Approach to Learning and Studying

Abstract: The purpose of this study was to explore the effects of concept mapping in developing critical thinking ability and approach to learning and studying. A quasi-experimental study design with a purposive sample was drawn from a group of nursing students enrolled in a medical-surgical nursing course in central Taiwan. Students in the experimental group were taught to use concept mapping in their learning. Students in the control group were taught by means of traditional lectures. After the intervention, the exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 17 publications
4
26
0
4
Order By: Relevance
“…Referring to the age of the respondents, the majority of respondents were 20 years and younger with an average age of 21 years. This finding is consistent with previous research by Brady (2005), Tiwari et al (2006) and Chen et al (2011) who also found the same average age of 20 years. Distribution of respondents based on their local origin indicates that more than half of respondents came from Java Island (PBL, n = 65, 52.4% and Non-PBL, n = 73, 58.9%) ( Table 3).…”
Section: Resultssupporting
confidence: 83%
“…Referring to the age of the respondents, the majority of respondents were 20 years and younger with an average age of 21 years. This finding is consistent with previous research by Brady (2005), Tiwari et al (2006) and Chen et al (2011) who also found the same average age of 20 years. Distribution of respondents based on their local origin indicates that more than half of respondents came from Java Island (PBL, n = 65, 52.4% and Non-PBL, n = 73, 58.9%) ( Table 3).…”
Section: Resultssupporting
confidence: 83%
“…The combination of these studies in a meta-analysis, including 362 participants, demonstrated the effectiveness of PBL (SMD=0.32, 95% CI=0.08 to 0.56; Overall Z=2.67, p=0.0078) when compared to lectures for the development of overall CT in undergraduate nursing students (Figure 3), with homogeneity being demonstrated (Chi-square=6.1, p=0.1068) between the studies. Three RCTs were also included that used the concept map as intervention and traditional teaching on the control group (15)(16)34) . The combination of these studies in one metaanalysis, including 251 participants, did not demonstrate effectiveness of the concept map (SMD=-0.53, CI 95% -0.79--0.28; Overall Z=4.07, p<0.0001) when compared to traditional education for development of overall CT in undergraduate nursing students (Figure 4).…”
Section: Meta-analysismentioning
confidence: 99%
“…This map allows students to associate their previous knowledge with each other, establish a link between this knowledge and newly acquired knowledge, and organize their plans reasonably (Austin Community College District, n.d.). It was determined in studies carried out with nursing students that the use of concept mapping enhanced the critical thinking scores of students during the term when they had not attended clinical practice yet, and that this method, for this reason, encouraged students to think critically (Atay & Karabacak, 2010;Chen, Liang, Lee & Liao, 2011;Lee et al, 2013;Pickens, 2007). Research investigating the effect of concept map use on the critical thinking and problem solving skills of nursing students in our country is limited.…”
Section: Introductionmentioning
confidence: 99%